An alternative observable to estimate keff in fast ADS. (September 2016) - Chersola, D.; Ricco, G.; Ripani, M.; Saracco, P.
Highlights: Alternative method for determining k eff in fast subcritical systems. Connection between neutron spectrum and k eff in fast subcritical systems. Study of lead, gas and sodium fast subcritical systems. Common trend of R ( k eff ) in lead and gas reactors. Trend quite similar for sodium reactors. Abstract: In this paper we examine an alternative method for determining the neutron multiplication factor k eff in fast subcritical reactors, based on the observable obtained by calculating the ratio between the "fast" component of the neutron flux (in this case by fast we mean neutrons with kinetic energy above 0.5 MeV) and the whole flux at all energies. The assumption behind the present study was that the above mentioned observable would be only sensitive to k eff, provided a peripheral fuel rod is considered (i.e. far from the neutron source in subcritical systems) and k eff is sufficiently high. Indeed, our results show that, for k eff > 0.7, the ratio calculated for LFR or GFR models turns out to show a quite similar trend well approximated by a straight line, while a different slope is observed for a sodium reactor. In our opinion, the results obtained show that such observable, after appropriate calibrations on the real systems under consideration, may be used for determining k eff in all operational conditions, in particular for subcritical systems with different types of neutron source and different values of the beam current.